DEVELOPMENT OF MOBILE-BASED FREELANCE SERVICES MARKETPLACE WITH FEATURE-DRIVEN DEVELOPMENT METHODOLOGY - Nurdiansyah, Mochamad Ikhsan; Kusumo, Dana Sulistyo; Ramadhan, Arief (Jurnal Teknik Informatika (Jutif), 2024)
The rapid advancement of technology demands that humans adapt to the evolving workplace. One of the impacts of technological development is the emergence of freelancers who use online platforms. Online platforms make it easier for freelancers and clients to collaborate. Currently, there are various Freelance Services Marketplace platforms available. However, it is important to note that the developers of these platforms are from outside Indonesia, which poses a risk to the security of people's data and the ease of payment applicable in Indonesia. With the high number of mobile device users in Indonesia,, the development of a mobile-based Freelance Services Marketplace application system that is tailored to local needs and takes into account the data security of Indonesian people, as well as involving local developers, is needed. This research aims to overcome these problems by designing a mobile-based freelance services marketplace application system using the Feature-Driven Development (FDD) method. The selection of FDD as an application development methodology is based on complex feature requirements, good planning management, emphasis on feature quality, and structured. The development process follows the FDD approach starting from feature planning and design, scheduling, implementation, and testing. The application design in this research is based on user needs with a focus on the features needed. This solution is important because it can be used by clients to find freelancers who match their needs and provide opportunities for freelancers to offer their services properly with guaranteed data security and transactions. The main result of this research is that the FDD method can help in the development of a freelance service marketplace application by paying attention to the systematic or structured level, quality, and security of the application.